Small Cell Carcinoma of the Esophagus: A case report and literature review - Guimarães , José Luiz Mirando (2022)
A case of primary small cell carcinoma in the lower third of the thorack esophagus in a 54- years old white man is presented. The initial symptoms was weight loss and epigastric pain in the last 3 months. The physical examination showed the evident signs ofthe constitutional disease. Accurate clinical staging was performed and revealed metastases in para-aortic, mesenteric and celiac lymph nodes. This case was characterized by a possible extensive local growth with invasion to the aorta. The treatment performed was systemic chemotherapy with cisplatin and etoposide (VP-16) combined with radiotherapy. Afier 3 courses of chemotherapy the complete clinical remission was achieved, and to consolidate the local result, the patient received externai beam irradiation and further chemotherapy with the same drugs. However, the local and systemic progression occurred 40 days after the radiotherapy. He died nine months after admission of respiratory infection with multiple metastases. We discuss the prognosis and the biological behavior of this aggressive disease and make the critical analysis of the therapeutic options. The main treatment for the advanced primary small cell carcinoma ofthe esophagus is based in systemic chemotherapy.